The Effect of Sharia Governance and Customer Relationship Marketing on Muzakki Loyalty - Mahmudi, Mahmudi; Prastmawati, Rizka Luluh (AKRUAL: Jurnal Akuntansi, 2020)
This study aims to analyze the effect of sharia governance and customer relationship marketing on muzakki loyalty. In this study, sharia governance was divided into six variables, i.e. transparency, accountability, responsibility, independence, fairness, and sharia compliance. Whereas customer relationship marketing was divided into four variables, i.e. trust, communication, commitment, and customer intimacy. We employed survey as a preferred method to obtained data. The samples of this study consisted of 200 muzakki (zakat payer) at amil zakat institutions (LAZ) in Yogyakarta, Indonesia. The data was analyzed using OLS regression techniques. The results of this research found that transparency, fairness and sharia compliance have a positive significant effect on customer loyalty, while accountability, responsiveness, and independency do not have significant effect on customer loyalty. Regarding the variable of customer relationship marketing, the result showed that communication, trust, and customer intimacy have a positive and significant effect on muzakki loyalty while commitment has no effect. It can be inferred that sharia governance and customer relationship marketing partially have a positive effect on muzakki loyalty.